(untitled) (Nigerian Journal of Technology, 2014)
An equation for sludge dewatering using FMTLxLyLz dimensional analysis approach has been presented. A pilot plant made of 12mm thick steel plate was used in designing a drying bed, 1.20m long, 0.75m wide, 0.80m deep with a total area of 0.90m2 and was used in dewatering sewage sludge from the University of Nigeria, Nsukka, waste water treatment plant. Parameters affecting filtration processes were used to derive an equation using dimensional analysis approach. The derived equation based on the concept of specific resistance, was used to investigate the performance of the sand drying bed as a sludge dewatering option. On verification using the experimental data obtained from the sewage plant, the theoretical prediction of the derived equation gave a close relationship to the practical values with a correlation of 0.994. The specific resistance from the experimental data was found to increase as the hydrostatic pressure increases numerically. Also, when ferric chloride was used to verify the effect of chemical conditioner on the sludge, it was observed that the specific resistance decreases with increasing dosage of chemical with the following results: Dosage increase of 10g, 20g, 30g, 40g and 50g of ferric chloride gave specific resistance decrease of 1.2271x 108m/kg, 0.4998 x 108m/kg, 0.29803 x 108m/kg, 0.18124 x 108m/kg, 0.075466 x 108m/kg respectively. Equally, when the effect of dilution was investigated, the specific resistance showed a decrease in value with increasing initial solid content. The experimental results obtained were in accordance with earlier studies done by other researchers.